Answer:
$5.82
Step-by-step explanation:
Answer:
The answer is (x + 3) (x - 7) = 0
Step-by-step explanation:
x² - 4x = 21
x² - 4x - 21 = 0
x² - 7x + 3x - 21 = 0
x(x - 7) + 3(x - 7) = 0
(x + 3) (x - 7) = 0
Thus, The answer is (x + 3) (x - 7) = 0
<em><u>-TheUnknownScientist</u></em>
Answer:
Step-by-step explanation:I think it's the 2nd one
Let's call the two numbers a and b. So we know that the difference of the two numbers is 36:
a - b = 36
And we know that their sum is 286:
a + b = 286
We can use either of these equations to solve for one of the variables in terms of the other variable. Let's use the first and solve for a:
a - b = 36
a = 36 + b
Now we plug this into the other equation and solve for b there:
(36 + b) + b = 286
36 + 2b = 286
2b = 250
b = 125
Answer:
10 more than fraction 1 over 4 of the sum of 5 and 3, then subtract 3
Step-by-step explanation:
Can't be the other ones